Kelemahan Negara dalam Pelanggaran APK Pemilu Serentak 2019 Kota Denpasar - Shah, Irfan; Putra Erawan, I Ketut; Mahaswari J.M, A.A.Sagung Mirah (Jurnal Nawala Politika, 2019)
ABSTRACT This research aimed to determine the factors behind the poor response of the state to the campaign props violations in Denpasar City. As the research framework, this research used the state in society theory and collective action theory. This research used the case study method. The findings represented that political power in various government institutions was the reason behind the state’s weakness in overcoming the campaign props violations. Through images and practices in the campaign props phenomenon, it can be seen that the relationship between the state and political parties was caused by the transformation of society through political parties for the purpose of domination. Conditions created by the images, practices, and transformations led to various impacts, from collective action in political parties to the occurrence of free riders by political parties inside and outside the coalitions, which increased the number of campaign props violations. Key Words: Campaign prop violations, Election Supervisory Board, Political parties, Denpasar